Pediatrics for medical students - Bernstein, Daniel; Shelov, Steven P.; Bernstein, Daniel, 1953- (Philadelphia : Wolters Kluwer Health/Lippincott Williams & Wilkins, 2012)
Textbook concentrates on evaluative skills and the rational development of differential diagnosis. It also covers clinical practice in the context of recent trends in the delivery of health care, including legal issues, coding, utilization review, utilization management and more.
Includes bibliographical references and index.
Includes bibliographical references and index.
All age.
Keywords: Pediatrics -- Textbooks; Pediatrics